Optimalisasi Penyuluhan Literasi Komputer sebagai Strategi Pemanfaatan Media Sosial di Banda Aceh - Nazaruddin Ali Basyah; Irham Fahmi; Ismail Ali; Irma Anggraini (ABDIKAN: Jurnal Pengabdian Masyarakat Bidang Sains dan Teknologi, 2023)
In today's era, marked by rapid advancements in communication methods and an abundance of information, computer literacy has become an urgent necessity for university students. Computers play a central role in both administrative and academic transactions, starting with semester registration, which is primarily conducted online. Computer culture possesses distinctive characteristics and advantages that set it apart from other fields of study. However, the concept of computer culture cannot be universally defined, and its levels are difficult to ascertain, as the competencies of computer-educated individuals vary from person to person and over time. What may be considered a luxury in one country may be deemed a necessity in another. To assess and gauge the level of computer culture among university students, a computerized scale consisting of 40 items with five multiple-choice alternatives was developed. Additionally, a 21-item computerized scale was created to determine their proficiency in electronic information retrieval, utilizing a five-point Likert scale. The results indicate that the students possess computer literacy and are skilled in searching for information electronically.